2016
DOI: 10.1080/87565641.2016.1243111
|View full text |Cite
|
Sign up to set email alerts
|

Visual Event-Related Potentials to Novel Objects Predict Rapid Word Learning Ability in 20-Month-Olds

Abstract: In an event-related potentials (ERP) study, twenty-month-old children (n = 37) were presented with pseudowords to map to novel object referents in five presentations. Quicker attenuation of the visual Negative central component (Nc) to novel objects predicted a larger difference in N400 amplitude between congruous and incongruous presentations of pseudowords at test. Furthermore, better initial recognition of familiar objects (Nc difference between familiar and novel objects) predicted the strength of the N400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Interestingly, further investigations have shown that the auditory preference is still present in later childhood at four years of age, yet ultimately disappears in adulthood, where adults exhibit a visual preference ( Robinson and Sloutsky, 2004 ; Sloutsky and Napolitano, 2003 ). In light of the advantageous status of the auditory modality in early infancy it is notable that the majority of electrophysiological research on early word learning has been conducted in cross-modal experiments (e.g., Borgström et al, 2016 , 2015a , b , Friedrich and Friederici, 2008 , 2011 , 2017 ; Friedrich et al, 2017 ; Torkildsen et al, 2008 , 2009 ). Thus, by exploring paradigms presenting objects in other than the visual modality, for example, audition, we can begin to understand how different types of perceptual information affect the building of object-word associations early in life, such as the meanings for auditory words like lullaby , siren , and thunder .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, further investigations have shown that the auditory preference is still present in later childhood at four years of age, yet ultimately disappears in adulthood, where adults exhibit a visual preference ( Robinson and Sloutsky, 2004 ; Sloutsky and Napolitano, 2003 ). In light of the advantageous status of the auditory modality in early infancy it is notable that the majority of electrophysiological research on early word learning has been conducted in cross-modal experiments (e.g., Borgström et al, 2016 , 2015a , b , Friedrich and Friederici, 2008 , 2011 , 2017 ; Friedrich et al, 2017 ; Torkildsen et al, 2008 , 2009 ). Thus, by exploring paradigms presenting objects in other than the visual modality, for example, audition, we can begin to understand how different types of perceptual information affect the building of object-word associations early in life, such as the meanings for auditory words like lullaby , siren , and thunder .…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, the N400 component has been found in many experiments on semantic priming, including language/word-learning in adults (e.g. Bentin et al, 1985 ; Boddy, 1986 ; Kutas and Federmeier, 2011 ; Kutas et al, 1984 ) and children (e.g., Borgström et al, 2016 , 2015a , b , Friedrich and Friederici, 2008 , 2011 , 2017 ; Friedrich et al, 2017 ; Torkildsen et al, 2008 , 2009 ). Note, that the N400 component does not only occur in the context of spoken and written words, but also for semantic processing difficulties in non-linguistic materials ( Cummings et al, 2006 ; Koelsch et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…A region of interest was selected for each effect, based on visual inspection of the largest differentiation between congruous and incongruous conditions. For the measures of the shape and regular N400 effects, the entire parietal region was selected (the same electrodes as in previous publications on this data set, Borgström et al, 2015a, b, 2016). The shape late negativity effect was calculated based on the entire central region (also corresponding to the electrode groupings in previous publications).…”
Section: Methodsmentioning
confidence: 99%
“…1The toddler data presented in this paper were part of a large project investigating several different aspects of semantic processing and word learning at 20 and 24 months, and the results have been reported previously (Borgström et al, 2015a, b, 2016). The present study focused on the relation between these toddler data and behavioral data from the same children that were collected 4½–5 years later.…”
mentioning
confidence: 95%
“…In particular, unlike ordinary least squares, LME can model fixed effects at the trial level, which is especially advantageous for developmental ERP studies. To illustrate, some ERP components show an amplitude ‘decay’ (habituation) over repeated trials (e.g., the Negative Central or NC; Borgström et al, 2016 ; Friedrich and Friederici, 2017 ; Junge et al, 2012 ; Karrer et al, 1998 ; Nikkel and Karrer, 1994 ; Reynolds and Richards, 2019 ; Snyder et al, 2010 ; Wiebe et al, 2006 ; but see also Quinn et al, 2006 , Quinn et al, 2010 ; Snyder et al, 2002 ). In ordinary least squares that cannot model trial-level variability, early trials will be mean averaged with later trials.…”
Section: Introductionmentioning
confidence: 99%